Super-Resolution Microscopy Reveals That Stromal Interaction Molecule 1 Trafficking Depends on Microtubule Dynamics - Huang, Yi-Ting; Hsu, Ya-Ting; Chen, Yih-Fung; Shen, Meng-Ru (Frontiers in Physiology, 2021)
Store-operated Ca2+ entry (SOCE) is an essential pathway for Ca2+ signaling, and regulates various vital cellular functions. It is triggered by the endoplasmic reticulum Ca2+ sensor STIM1. Illustration of STIM1 spatiotemporal structure at the nanometer scale during SOCE activation provides structural and functional insights into the fundamental Ca2+ homeostasis. In this study, we used direct stochastic optical reconstruction microscopy (dSTORM) to revisit the dynamic process of the interaction between STIM1, end-binding protein (EB), and microtubules to the ER-plasma membrane. Using dSTORM, we found that“powder-like”STIM1 aggregates into“trabecular-like”architectures toward the cell periphery during SOCE, and that an intact microtubule network and EB1 are essential for STIM1 trafficking. After thapsigargin treatment, STIM1 can interact with EB1 regardless of undergoing oligomerization. We generated STIM1 variants adapted from a real-world database and introduced them into SiHa cells to clarify the impact of STIM1 mutations on cancer cell behavior. The p.D76G and p.D84Y variants locating on the Ca2+ binding domain of STIM1 result in inhibition of focal adhesion turnover, Ca2+ influx during SOCE and subsequent cell migration. Inversely, the p.R643C variant on the microtubule interacting domain of STIM1 leads to dissimilar consequence and aggravates cell migration. These findings imply that STIM1 mutational patterns have an impact on cancer metastasis, and therefore could be either a prognostic marker or a novel therapeutic target to inhibit the malignant behavior of STIM1-mediated cancer cells. Altogether, we generated novel insight into the role of STIM1 during SOCE activation, and uncovered the impact of real-world STIM1 variants on cancer cells.